2020
DOI: 10.1371/journal.pone.0232917
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic pentapeptide cRGDfK enhances the inhibitory effect of sunitinib on TGF-β1-induced epithelial-to-mesenchymal transition in human non-small cell lung cancer cells

Abstract: In human lung cancer progression, the EMT process is characterized by the transformation of cancer cells into invasive forms that migrate to other organs. Targeting to EMT-related molecules is emerging as a novel therapeutic approach for the prevention of lung cancer cell migration and invasion. Traf2-and Nck-interacting kinase (TNIK) has recently been considered as an anti-proliferative target molecule to regulate the Wnt signaling pathway in several types of cancer cells. In the present study, we evaluated t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…Because of the high binding affinity and selectivity for integrin α δ β 3 and α δ β 5 in cancer cells, the use of cyclic peptides, such as cRGDfK and cRGDyK, has been one method for delivering therapeutic drugs in cancers (Chen and Chen, 2011;Kulhari et al, 2016). In a previous study, we confirmed that the cyclic pentapeptide containing the RGD motif (cRGDfK) enhances the inhibitory effect of TKI sunitinib on the TGF-β1-induced EMT (Park and Kim, 2020). The cRGDfK not only promotes the NSCLC cell death-inducing effect of gefitinib, but also increases the inhibitory effect on mesenchymal marker mRNA and protein expression.…”
Section: Discussionsupporting
confidence: 56%
“…Because of the high binding affinity and selectivity for integrin α δ β 3 and α δ β 5 in cancer cells, the use of cyclic peptides, such as cRGDfK and cRGDyK, has been one method for delivering therapeutic drugs in cancers (Chen and Chen, 2011;Kulhari et al, 2016). In a previous study, we confirmed that the cyclic pentapeptide containing the RGD motif (cRGDfK) enhances the inhibitory effect of TKI sunitinib on the TGF-β1-induced EMT (Park and Kim, 2020). The cRGDfK not only promotes the NSCLC cell death-inducing effect of gefitinib, but also increases the inhibitory effect on mesenchymal marker mRNA and protein expression.…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies show that the combination of antiangiogenic sunitinib with an αvβ3 integrin antagonist cRGDfK peptide displays a synergistic anticancer effect in human lung adenocarcinoma cells . In the present study, SRPIN803 and geo35 were identified to hold antiangiogenic activity in vivo in zebrafish embryos, and this effect was dose-dependent.…”
Section: Discussionsupporting
confidence: 49%
“…Cyclic peptides such as cRGDfK and cRGDyK exhibit high binding affinity and selectivity for the overexpressed integrins α ν β 3 and α ν β 5 in cancer cells, facilitating the delivery of anticancer drugs to the target [ 41 , 42 ]. We recently demonstrated that cRGDfK increased NSCLC apoptosis and enhanced the inhibitory effects of the TKI sunitinib on TGF-β1–induced EMT [ 43 ]. Single compound treatment with TKI involves toxic effects at high concentrations, but in that study, EMT could be effectively inhibited when a cyclic peptide was added to a low concentration of TKI in combined treatment.…”
Section: Discussionmentioning
confidence: 99%